Pengaruh Konsentrasi Kalium Silikat (K2SiO3 ) terhadap Faktor Virulensi dan Patogenesitas Ralstonia Solanacearum - Irbah Fawwas Salsa Billa (Fakultas Pertanian, 2026)
Bacterial wilt disease is one of the important diseases in tomato plants caused by infection of the bacterium Ralstonia solanacearum. This study aims to examine the effect of potassium silicate (K2SiO3) concentration on the virulence and pathogenicity factors of Ralstonia solanacearum. In this study, potassium silicate treatment was given to Ralstonia solanacearum inoculum with different concentrations to observe changes that occur in virulence factors, such as the production of exopolysaccharides (EPS), Endoglucanase (EGL), and pectinase enzyme production as well as the ability of bacteria to cause disease (pathogenicity). The concentrations used consisted of 5 mM, 10 mM, 15 mM, and 20 mM. The results showed that potassium silicate (K2SiO3) treatment was able to significantly increase the percentage of exopolysaccharide (EPS) production, and pectinase enzyme production which was indicated by the high value of the pectolytic index produced by Ralstonia solanacearum bacteria. In endoglucanase (EGL) testing, potassium silicate (K2SiO3) treatment increased cellulase enzyme production in the first 24 hours. This was indicated by a higher cellulolytic index value compared to the control treatment. However, after 72 hours of observation, the cellulolytic index value was lower than the control treatment. The cellulolytic index at a concentration of 20 mM showed a high value in the first 24 hours and production was suppressed in the following 24 hours. Application of potassium silicate (K2SiO3) to infected tomato plants showed a higher percentage of disease severity compared to the pathogen control treatment, resulting in more severe tissue damage.
Reupload File Repository 21 Mei 2026_Yudi Validasi_26 Mei 2026_Yudi_Naomy
Keywords: Ralstonia solanacearum; K2SiO3; Virulence; Pathogenicity